2010
DOI: 10.1016/j.hrtlng.2009.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Cultural factors facilitating cardiac rehabilitation participation among Canadian South Asians: A qualitative study

Abstract: Previous research identified barriers to CR participation in the South Asian community, and this study is the first to identify facilitators. Results suggest that families should be included in patient-education sessions, CR should be reinforced by healthcare providers, and the provider team should recognize cultural preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 49 publications
1
57
0
4
Order By: Relevance
“…32 Being female (39.6% versus 49.4% for men), 41 and having a lower socioeconomic status (SES) (61.4% for lower SES versus 68.1% for higher SES, p<0.01) 42 decreased this possibility (Table 1). 17,41,[43][44][45] Support for the concept that the low referral rate of female patients is due to clinician belief was found in a study of physicians' judgments of the suitability of patients for CR.…”
Section: Clinicians' Beliefsmentioning
confidence: 99%
“…32 Being female (39.6% versus 49.4% for men), 41 and having a lower socioeconomic status (SES) (61.4% for lower SES versus 68.1% for higher SES, p<0.01) 42 decreased this possibility (Table 1). 17,41,[43][44][45] Support for the concept that the low referral rate of female patients is due to clinician belief was found in a study of physicians' judgments of the suitability of patients for CR.…”
Section: Clinicians' Beliefsmentioning
confidence: 99%
“…Conducting an EEA includes identifying antecedent or predisposing, enabling, and reinforcing factors that may contribute to health-behavior change and maintenance. Predisposing factors include an array of preexisting conditions that may influence behavior change in a given population, such as individual beliefs, attitudes, personal preferences, motivation, and existing skills and knowledge (Banerjee, Grace, Thomas, & Faulkner, 2010;Gielen, McDonald, Gary, & Bone, 2008). Enabling factors include variables that may facilitate, catalyze, or stimulate motivation for actually engaging in behavior change, such as available resources and new skills.…”
Section: Trans-positive Carementioning
confidence: 99%
“…Enabling factors include variables that may facilitate, catalyze, or stimulate motivation for actually engaging in behavior change, such as available resources and new skills. Finally, reinforcing factors of behavior change and maintenance include determinants that are likely to sustain behavior change in a group of individuals, such as social support and peer influence (Banerjee, Grace, Thomas, & Faulkner, 2010;Gielen, McDonald, Gary, & Bone, 2008).…”
Section: Trans-positive Carementioning
confidence: 99%
See 1 more Smart Citation
“…While literature investigating cultural influences in cardiac rehabilitation is scarce, a study by Banerjee et al showed that while SA patients were less likely to complete the entire 6‐month rehabilitation program compared to whites, they trended to a greater change in maximum metabolic equivalents, and more often reached at least 85% of their target heart rate. While important research has been recently published in this area using qualitative studies identifying enabling and reinforcing factors such as flexible rehabilitation programs and closer physician and family support, studies specifically evaluating cardiac rehabilitation practices following CABG are still lacking. Finally, dietary modifications have been shown to be effective, at least in the short term, after CABG .…”
Section: Discussionmentioning
confidence: 99%